No Simples, No Gunk, No Nothing. (3rd March 2014) - Cowling, Sam
Abstract Mereological realism holds that the world has a mereological structure – i.e. a distribution of mereological properties and relations. In this article, I defend Eleaticism about properties, according to which there are no causally inert non‐logical properties. I then present an Eleatic argument for mereological anti‐realism, which denies the existence of both mereological composites and mereological simples. After defending Eleaticism and mereological anti‐realism, I argue that mereological anti‐realism is preferable to mereological nihilism. I then conclude by examining the thesis that composition is identity and noting its consequences for the question of mereological structure.